Excavation of an urned cremation burial of the Bronze Age, Glennan, Argyll and Bute (Scottish Historical and Archaeological Internet Reports, 2003)
As part of the Historic Scotland Human Remains Call Off Contract, Glasgow University Archaeological Research Division (GUARD) undertook an archaeological excavation of a prehistoric urned cremation deposit within a boulder shelter at Glennan, Kilmartin, Argyll and Bute (NGR: NM 8622 0097). Analysis has shown the cremation was of a male probably aged between 25 and 40 years. He had suffered from slight spinal joint disease, and mild iron deficiency anaemia, though neither seems likely to have affected his general health. He was cremated shortly after death, together with a young sheep or goat, and their remains were subsequently picked from the pyre and co-mingled before burial in the urn. An unburnt retouched flint flake was recovered which may have accompanied the burial. The closest parallels for the cremation container are found within the tradition of Enlarged Food Vessel urns, a tradition that is poorly dated but probably has a currency in the first half of the second millennium BC.